PENGARUH PEMILIHAN UMUM SECARA SERENTAK 2019 TERHADAP SISTEM PRESIDENSIAL INDONESIA - Putra, I Gusti Ngurah Agung Krisna; Erawan, I Ketut Putra; Jayanthi Mertha, Anak Agung Sagung Mirah Mahaswari (Jurnal Nawala Politika; Vol 1 No 2 (2022): Jurnal Ilmu Politik, 2022)
In 2019, the General Election Commission (KPU) implemented a new system in a democratic party, namely concurrent general elections ( pemilu ), which means that the public can hold parliamentary elections ( Pileg ) and presidential election ( Pilpres ) at the same time in April. 17, 2019. Concurrent elections in 2019 have become a form of democratic party as well as an attempt to strengthen the presidential system in Indonesia, as presidential and vice-presidential candidates are no bound to establish the presidential threshold mechanism. As the title mentioned by the author, this documentary research paper aims to describe the 2019 concurrent elections probably can influence the presidential system in Indonesia by gathering opinions. knowledge from a number of books and articles that raise discussions regarding general elections and the presidential system.